A Multi-microgrids System Model Considering Stochastic Correlations Among Microgrids. (July 2018) - Zhang, Xingyou; Chen, Bo; Cheng, Yan; Sun, Shumin; Wang, Shouxiang
Abstract: This paper proposes a multi-microgrid system reliability model which considers stochastic correlations among microgrids. Unlike traditional microgrid model, the proposed model can consider stochastic correlations among output of distributed generators and stochastic correlations among loads which is belonging to different microgrids. Using historical data, it shows that the proposed model helps to simulate the stochastic correlations among different microgrids. Furthermore, this paper also proposes a reliability assessment algorithm which incorporates the proposed model. Finally, the proposed model and algorithm are applied to a multi-microgrid system reliability evaluation case, which shows that the proposed stochastic model and algorithm can be effectively utilized by planners to conduct reliability evaluation of a multi-microgrid system.